The role of myocardial performance index and Nt-proBNP levels as a marker of heart dysfunction in nonalcoholic cirrhotic patients - TOKAY TARHAN, SENA; EREN, FATİH; FAK, ALİ SERDAR (My University, 2022)
Objective: Cardiac dysfunction has been reported in both cirrhotic and alcoholic patients. Our aim was to determine the relation of serum N-terminal pro-B-type natriuretic peptide (Nt-proBNP) levels to myocardial performance index (MPI) and disease severity in nonalcoholic cirrhotic patients. Patients and Methods: In this prospective study including 25 cirrhotic patients and 27 healthy controls, MPI was assessed by pulsedwave tissue Doppler imaging (PW-TDI). The disease severity was determined by Child–Turcotte–Pugh (CTP ) and model for endstage liver disease (MELD) scores. Results: There were no statistically significant differences in MPI levels between patients and controls (p< 0.246). Nt-proBNP levels (p< 0.0003), cardiac output (CO) (p< 0.0002), left ventricular end-systolic (LVES) volume (p< 0.031) and QT interval (p< 0.0001) increased and left ventricular systolic function was normal in all cirrhotic patients when compared to controls. Nt-proBNP levels were positively correlated with MELD scores (p< 0.0001, r= 0.59), QT duration (p< 0.0001, r= 0.59), CO (p= 0,001, r= 0.44), right atrial (RA) area (p= 0.026, r= 0.31) and negatively correlated with diastolic BP (p= 0.015, r= – 0.34). Conclusion: We conclude that in nonalcoholic cirrhotic patients, left ventricular MPI and systolic function were normal. Nt-proBNP levels were correlated with the disease severity and hyperdynamic circulation.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Cirrhosis; Heart failure; Nt-proBNP; Echocardiography; BRAIN-NATRIURETIC PEPTIDE; VENTRICULAR DIASTOLIC DYSFUNCTION; TISSUE-DOPPLER; EUROPEAN ASSOCIATION; AMERICAN SOCIETY; FILLING PRESSURE; TEI INDEX; CARDIOMYOPATHY; ECHOCARDIOGRAPHY; SEVERITY; Cirrhosis; Heart failure; Nt-proBNP; Echocardiography